“THE ROLE OF ARTIFICIAL INTELLIGENCE AND GENERATIVE AI IN MODERN EDUCATION: OPPORTUNITIES AND CHALLENGES” (Journal of Universal Science Research, 2025)
This article explores the transformative role of Artificial intelligence in education and teaching.Additionally, it focuses on particularly generative AI technologies like CHatGPT.The study represents AI’s functions and its potential in different educational purposes like individual learning, creating engaging activities, lesson plans, how to manage time and students’ engagement in classes. Also, it gives a little bit information about AI in other fields and usage of AI by big companies as a main part of them. Some key points include the impact of AI in both teaching and learning.Furthermore, this research article discusses the contrubutions of early pioneers like who introduced the term "artificial intelligence.” In the article, scenarios of AI and functions are given by tables, the first table examines the role of artificial intelligen and second one highlights the functions of AI that can do in the teaching and education.